2006
DOI: 10.1182/blood.v108.11.3598.3598
|View full text |Cite
|
Sign up to set email alerts
|

Essential Thrombocythemia in Young Individuals: Frequency and Risk Factors for Vascular Events and Evolution to Myelofibrosis in 126 Patients.

Abstract: Vascular events and evolution to either myelofibrosis (MF) and acute leukemia (AL) are the main causes of morbidity and mortality in individuals with essential thrombocythemia (ET). However, the frequency of these complications in young ET patients is not well known. The objective of the present study was to assess the frequency of vascular events and the incidence of MF and AL in young patients with ET and to identify the factors associated with the development of such complications. In 126 subjects diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…In Vannucchi et al (2007a), the independent association was only with rare homozygous‐mutant cases, in Kittur et al (2007) the association was lost if prior thrombosis was incorporated into the model, and in Heller et al (2006), the majority of the thrombotic events occurred prior to or at diagnosis. Four studies refuted the association between JAK2 V617F mutation status and thrombotic risk (Wolanskyj et al , 2005; Tefferi et al , 2006; Alvarez‐Larran et al , 2007; Carobbio et al , 2007), though these tended to include fewer patients, and analysed arterial and venous events together. Consequently, they may not have detected small differences in rates of vascular events between the V617F‐positive and the V617F‐negative groups, particularly differences confined to either arterial or venous subtypes.…”
Section: Jak2v617f and Thrombosis In Mpdmentioning
confidence: 99%
“…In Vannucchi et al (2007a), the independent association was only with rare homozygous‐mutant cases, in Kittur et al (2007) the association was lost if prior thrombosis was incorporated into the model, and in Heller et al (2006), the majority of the thrombotic events occurred prior to or at diagnosis. Four studies refuted the association between JAK2 V617F mutation status and thrombotic risk (Wolanskyj et al , 2005; Tefferi et al , 2006; Alvarez‐Larran et al , 2007; Carobbio et al , 2007), though these tended to include fewer patients, and analysed arterial and venous events together. Consequently, they may not have detected small differences in rates of vascular events between the V617F‐positive and the V617F‐negative groups, particularly differences confined to either arterial or venous subtypes.…”
Section: Jak2v617f and Thrombosis In Mpdmentioning
confidence: 99%
“…It is, therefore, important to consider the current findings as being preliminary and in need of validation by additional studies that are designed to offset potential test limitations. Future studies should also include adequate numbers of informative cases with leukemic and fibrotic progressions, as well as thrombotic events, in order to assess LDH impact on such events, in the context of previously identified risk factors for thrombosis (advanced age, presence of JAK2 V617F and MPL , and history of thrombosis), leukemic transformation (thrombosis history, platelets >1 million/μL, leukocytosis, age >60 years) and fibrotic progression (anemia, age >60 years, male sex, increased BM reticulin fibrosis, presence of MPL mutation, and elevated serum LDH) …”
Section: Discussionmentioning
confidence: 99%
“…Survival of patients in the different MPN entities has been reported in several cohort studies; the majority of reports have shown a significantly shorter survival of patients with PV compared to the normal population (8, 13, 31, 32). On the other hand, several retrospective studies of groups of patients with ET have proved no or little effect on life expectancy compared with the normal population (8, 33–35). Our cohort of 280 patients diagnosed with PV or ET, with the use of the PVSG criteria, in the city of Gothenburg, Sweden, studied between 1983 and 1999 confirm these observed differences in survival expectancy.…”
Section: Discussionmentioning
confidence: 99%